2013
DOI: 10.1155/2013/274805
|View full text |Cite
|
Sign up to set email alerts
|

Antibody‐Conjugated Rubpy Dye‐Doped Silica Nanoparticles as Signal Amplification for Microscopic Detection of Vibrio cholerae O1

Abstract: This study demonstrated the potential application of antibody-conjugated Rubpy dye-doped silica nanoparticles for immunofluorescence microscopic detection ofVibrio choleraeO1. The particle synthesis of 20X of the original ratio was accomplished yielding spherical nanoparticles with an average size of45±3 nm. The nanoparticles were carboxyl functionalized and then conjugated with either monoclonal antibody or polyclonal antibody againstV. choleraeO1. The antibody-conjugated nanoparticles were tested with two ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The size of FDS-NPs of approximately 30-60 nm was consistent with that previously reported [14,15,17,18]. Thepwiwatjit et al [14] reported the FDS-NPs with relatively narrow size of 29-43 nm. The size distribution usually depended on synthesis techniques, equipment, time, maximum speed, size of magnetic stirrer, and container.…”
Section: Characteristics Of Fds-npssupporting
confidence: 89%
See 2 more Smart Citations
“…The size of FDS-NPs of approximately 30-60 nm was consistent with that previously reported [14,15,17,18]. Thepwiwatjit et al [14] reported the FDS-NPs with relatively narrow size of 29-43 nm. The size distribution usually depended on synthesis techniques, equipment, time, maximum speed, size of magnetic stirrer, and container.…”
Section: Characteristics Of Fds-npssupporting
confidence: 89%
“…Our research group had developed silica and ferromagnetic nanoparticle-based detection for Vibrio cholerae in seafoods, Salmonella spp., E. coli O157:H7, and C. jejuni in poultry and products [14][15][16][17][18]. These methods showed potential applications in the routine use.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Rubpy dye-doped silica nanoparticles (RSNPs) were synthesized using a water-in-oil microemulsion technique as described in [20]. Briefly, cyclohexane, aqueous Rubpy dye solution, Triton X-100, and n-hexanol were used as oil phase, water phase, surfactant, and cosurfactant, respectively.…”
Section: Synthesis Of Rubpy Dye-doped Silica Nanoparticlesmentioning
confidence: 99%
“…However, using these nanomaterials as detection particles requires specific equipment to detect or monitor their fluorescence signals such as spectrofluorometer [9,13], fluorescence microscope [9,17,20], confocal microscope [12,21] and flow cytometer [22]. This necessity might be the reason that there is no study reporting an employment of these materials in a strip assay for a point-of-care or field test although they have been of interest as a fascinating fluorescent probe and attracted widespread application in biology and medicine for years.…”
Section: Introductionmentioning
confidence: 99%